BRAC University new campus development project construction schedule (01.11.2021-30.11.2021) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding BRAC University new campus development project construction schedule from 01.11.2021 to 30.11.2021.